Common and snow leopards share prey, but not habitats: competition avoidance by large predators?. (28th August 2013) - Lovari, S.; Minder, I.; Ferretti, F.; Mucci, N.; Randi, E.; Pellizzi, B.
Abstract: Resource exploitation and behavioural interference underlie competition among carnivores. Competition is reduced by specializing on different prey and/or spatio‐temporal separation, usually leading to different food habits. We predicted that two closely related species of large cats, the endangered snow leopard and the near‐threatened common leopard, living in sympatry, would coexist through habitat separation and exploitation of different prey species. In central Himalaya, we assessed (2006–2010) habitat and diet overlap between these carnivores. The snow leopard used grassland and shrubland, whereas the common leopard selected forest. Contrary to our prediction, snow leopard and common leopard preyed upon similar wild (Himalayan tahr, musk deer) and domestic species ( Bos spp., dogs). Dietary overlap between snow leopard and common leopard was 69% (yearly), 76% (colder months) and 60% (warmer months). Thus, habitat separation should be the result of other factors, most likely avoidance of interspecific aggression. Habitat separation may not always lead to the use of different prey. Avoidance of interspecific aggression, rather than exploitation of different resources, could allow the coexistence of potentially competing large predators.